The Effectiveness of Powerpoint-Assisted Contextual Teaching and Learning on Students’ Critical Thinking Skills: A Case on Geometry Material - Murni, Sukma; Suryadi, Didi; Prabawanto, Sufyani; Herman, Tatang; Gumpita, Melly Terry ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
Based on the problems faced in schools from the results of interviews with the lack of student learning outcomes on the circumference and area of ​​flat shapes this is due to the lack of media and approaches used by classroom teachers, so researchers want to improve students' critical thinking skills by developing power point learning media assisted by the Canva application that can help students understand the material and various questions with critical thinking skills, as well as a contextual teaching and learning approach that makes students find out and be active in learning. The research method used is Research and Development from Borg and Gall with the following stages: 1) Research, 2) planning, 3) product development, 4) limited test, 5) Revision, 6) wider test, 7) final product . For the results of the teacher's response, 84% are in good category and 73% are in good enough category. For the results of improving students with the n-gain test, the limited trial was 0.65 and the broad trial was 0.66, including the medium category. The normality test in the limited test is 0.200 and 0.068 while for the broad test it is 0.256 and 0.813 so that the distribution is normal. Paired simples test in limited trials and wide trials 0.000 <0.05 then H0 is rejected, Ha is accepted. So there are significant and effective differences in learning.